The Importance of Modeling Carbon Dioxide Transportation and Geologic Storage in Energy System Planning Tools - Ogland-Hand, Jonathan D.; Cohen, Stuart M.; Kammer, Ryan M.; Ellett, Kevin M.; Saar, Martin O.; Bennett, Jeffrey A.; Middleton, Richard S. (Frontiers in Energy Research, 2022)
Energy system planning tools suggest that the cost and feasibility of climate-stabilizing energy transitions are sensitive to the cost of CO2 capture and storage processes (CCS), but the representation of CO2 transportation and geologic storage in these tools is often simple or non-existent. We develop the capability of producing dynamic-reservoir-simulation-based geologic CO2 storage supply curves with the Sequestration of CO2 Tool (SCO2T) and use it with the ReEDS electric sector planning model to investigate the effects of CO2 transportation and geologic storage representation on energy system planning tool results. We use a locational case study of the Electric Reliability Council of Texas (ERCOT) region. Our results suggest that the cost of geologic CO2 storage may be as low as 3/tCO2 and that site-level assumptions may affect this cost by several dollars per tonne. At the grid level, the cost of geologic CO2 storage has generally smaller effects compared to other assumptions (e.g., natural gas price), but small variations in this cost can change results (e.g., capacity deployment decisions) when policy renders CCS marginally competitive. The cost of CO2 transportation generally affects the location of geologic CO2 storage investment more than the quantity of CO2 captured or the location of electricity generation investment. We conclude with a few recommendations for future energy system researchers when modeling CCS. For example, assuming a cost for geologic CO2 storage (e.g., 5/tCO2) may be less consequential compared to assuming free storage by excluding it from the model.